Efeito microbiológico, índice de placa bacteriana, pigmentação dentária e percepção gustativa da clorexidina 0,12% com sistema antidescolorante, após exodontia de terceiros molares - Milleri, Daniela Pertel (2018)
Chlorhexidine (CHX) is an antiseptic widely used for the chemical control of bacterial plaque and as antimicrobial agent during the postoperative period of oral surgeries; its long-term use may induce adverse effects such as tooth staining, oral mucosa irritation and taste alterations. Objective: to evaluate the plaque index (PI), tooth color change (ΔE), microbiological effect and patients’ perception regarding the use of 0.12% CHX with Anti Discoloration System after third molar extractions. Methods: this prospective cross-over study involved 22 participants that used 0.12% CHX mouthwashes with and without ADS for 15 days each, with an interval of at least 15 days. Silness and Löe PI was recorded on central incisors and first molars; the color of central incisors was measured with a spectrophotometer and ΔE was calculated by using the formula ΔE=[(ΔL*)2+(Δa*)2+(Δb*)2 ] 0,5; the Streptococcus sp in saliva were quantified through Colony Forming Units (CFU); the patient's perception was obtained with the Visual Analogue Scale (VAS) for the following parameters: 1) taste of the product, 2) alteration in food taste, 3) changes in salt perception, 4) irritation of the oral mucosa. Results: a reduction of IP was observed for both groups, with no significant difference between incisors and canines (p>.05); however, molars presented higher IP for the CHX with ADS group (p=.011). ΔE for CHX with and without ADS groups were 2.95 and 3.85, respectively. A significant decrease in CFU/mL was found for both groups, albeit lower for CHX with ADS (p=.001). In the CHX with ADS group, alterations in food taste, changes in salt perception and irritation of the oral mucosa were significantly lower than CHX group (p<.05). Conclusion: both solutions were efficient in bacterial plaque control; ΔE was clinically unsatisfactory for CHX group and acceptable for CHX with ADS; the use of CHX without ADS resulted in significant reduction of CFU/mL; and participants reported less alteration in food taste, salt perception and irritation of the oral mucosa when CHX with ADS was used.